Fabrication and characterization of sawdust-reinforced mycelium biocomposite as alternative to expanded polystyrene packaging - Oh, Jacqueline Joyce H.; Oliquino, Zarra Jane A.
Polystyrene is a lightweight, brittle, and low cost polymer that is a nonbiodegradable, mostly non-recyclable, and requires crude oil, a non-renewable source. The goal of this research was to create a biocomposite using mycelium from locally produced oyster mushrooms to bind scrap sawdust. The optimum settings were determined by first making different ratios of sawdust and mushrooms in intervals of 10% by weight. Next, it was left to bind for five days, heat treated for 2 hours at 150°C to stop the mycelium growth, and allowed to dry for another week. The successful final products were subjected to compression and flexure testing. Their thermal properties were also determined using thermogravimetric analysis. The morphology was then studied under the scanning electron microscope. The appropriate settings obtained for creating the biocomposite was using ratios with mushroom content between 50-80% and heating the specimens for 2 hours at 150°C. The compression strength of the biocomposites was significantly higher than the compression strength of the expanded polystyrene. For the flexure strength, however, the one closest to the value of the EPS is the sample which is made with 80% mushroom. When subjected to heat up to 50°C, 7.058% to 8.154% of the biocomposite weight was reduced. The mycelium biocomposite fabricated in this experiment can be used to create packaging under low load bearing applications and can be used under ambient conditions without degrading the materia